Palatine suture obliteration method for age estimates of burn victims with minimal tooth remains: a case report - Prastyo, Eko; Sari, Fitri Ambar; Auerkari, Elza Ibrahim; Suhartono, A. Winoto; Pasaribu, Roben Suhadi; Soedarsono, Nurtami; Zevrianty, Dieci; Yunus, Aditia Dedek; Auerkari, Pertti (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2025)
Background: A disaster is a serious disruption in the functioning of a society that can cause many losses. It can be caused by nature or humans. When the loss of life is on a large scale, the recovery process is made more complicated by simultaneous identification operations. Biological profiling is of paramount importance when investigating cases; the age at which a victim dies is crucial for reconstructing the victim’s life. Purpose: The purpose of this case study is to highlight the utility of palatal suture obliteration as a valuable indicator for age estimation in adults, especially when there are minimal remaining dental elements that make age estimation by other methods of dental analysis impossible. Case: The author presents a case of burn victims due to a fire disaster in the fuel oil terminal area in Jakarta that killed several victims. As they were found in a visually unrecognizable condition, without identity documents, and in a state where the victims’ teeth left few dental elements, effort is needed to assist in identifying the victims, including victim age estimation techniques with ideal methods that can be applied in the field. Case management: The Crow-Glassman Scale (CGS) is used to describe the extent of burns to tissue remnants. On external examination, all body parts showed the burns reaching level 3 CGS. The victim is estimated to be over 50 years old. Decision making is based on the guidelines of the Mann method, wherein if more than 50% of the anterior median palatine suture is obliterated, then the minimum estimated age is 50 years. Conclusion: The obliteration of the palatal sutures can be used as supporting evidence when considered alongside other more reliable age indicators that can narrow down the age of unidentified individuals.